Repeat, Reproduce, Replicate. - Neville-Neil, George V. (Communications of the ACM, 2024)
This article presents a question from a reader about the quality of code presented in research articles in terms of its reproducibility. The answer to the question takes a look at the Association of Computing Machinery’s badging system for software artifacts, scientific method and the “publish or perish” mentality in academia.